(untitled) (Archives of Criminology, 1982)
The present paper is a report on the studies conducted in the years 1975-77, dealing with a group of young regularly excessively drinking men aged 18-25. The population from which the sample was randomly drawn consisted of men aged 18-25 inhabiting 4 of the 7 districts of Warsaw and reported by the district constables of the police as persons regularly excessively drinking (that is, getting drunk more frequently than once a week). The district constables reported the total of 1,273 men meeting the above criteria, which makes about 3% of the number of all men of this age living in these districts. In reality, the percentage of men of this age regularly excessively drinking is probably much higher, as a considerable number of constables stated that they worked in their districts for too short a period to know all the persons living there who would qualify for the study. From the mentioned population, 331 persons were randomly drawn for the study. The materials employed consist of interviews with the mothers of the examined persons and of information from official sources court records, prison files, documents of juvenile courts and detoxication centres. The similar data were gathered as regards all brothers of the examined persons who were also aged 18-25. When beginning the study, it was acknowledged that considering the criteria for the selection of the population, first of all persons with negative family background would be selected and that this very environmental characteristic would be the main determinant of differentiating the main group from the control group, where the family background - as it was easy to foresee - would be of a more favourable character. It was thus decided to eliminate the influence of family background variable in the selection of the control group, so as to render possible the protrusion - of other characteristics which differentiate the persons regularly excessively drinking from those of the control group. Considering this, the control group was made of all brothers of the examined persons who were also aged 18-25 but were not reported by the district constables as regularly excessively drinking. There were 111 brothers meeting these criteria, and they make the control group in the present study. The first part of the study was to verify if the family background of the examined persons and those included in the control group was indeed as negative as presumed. In this case, the hypnothesis was fully confirmed. Among the 311 families of those examined as many as 166 (53,3%) were one-parent or broken families which dated back to the time when the persons under examination had been minors. The families were in general numerous, average being 3 children per family, while there were 88 (28.3%) families with 4 or more children. For the further characterization of the families the data regarding fathers were employed. It turned out that 158 (50.8%) fathers were regularly excessively drinking; in fact in the majority of cases they were alcoholics. At least 98 (31.5%) fathers were convicted by courts and 91 (29.3%) by the Penal Administrative Commissions. Taking all these three characteristics together, it was stated that as many as 194 (62,4%) fathers were regularly excessively drinking or had criminal records. These data point to the large intensity of pathological phenomena in the families of persons under examination and their brothers from the control group. And yet on the other hand, taking into account the social and professional status (education and profession) of the fathers, their situation in this respect was found better than supposed, though they belonged to the lower social classes. The second part of the study deals with the extent of social maladjustment of persons under examination and their brothers from the control group. Apart from the fact that - according to the principles of sample selection - all the persons should have been regular heavy drinkers, the gathered data were verified in respect of their confirmation of this fact. As regularly excessively drinking the persons were recognized who - according to their mother’s statements - got drunk more often than once a week or had been taken into the detoxication entre. There were 253 (76.4%) such persons in the main group and 44 (40%) in the control group. Also, a category of persons who drank most frequently was distinguished, those who were probably alcoholics. In this category there were included persons who - according to their mothers’ statements - got drunk at least twice a week or had been taken into the Detoxication Centre at least three times. There were 122 (37%) such persons in the main group, and 17 (16%) in the control group. As to the symptoms of social maladjustment, they were decidedly greater in the main group than in the control group, which dated back as far as their childhood. And so, for instance, severe school problems (uncompleted elementary education or repeating classes) were found in 60.7% of the examined persons and in 42.3% of their brothers from the control group. 57.1% of the examined persons and 30.6% of their brothers from control group committed thefts outside their home and respectively 23.9% and 10.8% were placed in reformatories in consequence of their stealing. The differences in the extent of social maladjustment among both groups increased with age, and grew particularly large in the age of adulthood. And so, as many as 57.1% of the examined persons stayed out of work or worked irregularly as compared with 21.6% of their brothers from the control group. Suicidal attempts and self-injuries were performed by 29.3% of persons under scrutiny and by 9% of their brothers from the control group. There are also obvious differences as to the extent of delinquency in both groups. 42% of the persons examined and only 17.1% of their brothers had action brought against them in Penal Administrative Commissions and 60.1% of the persons examined and 28.8% of their brothers were convicted by court. Taking into account those convicted by court only, the percentage of recidivists was 50.8% in the test group and 46.9% in the control group, whereas the character of delinquency was similar in both groups, the majority being violent offences. Considering the fact that the control group consisted of brothers of the examined persons who were also aged 18-25, the great difference in the occurrence of the symptoms of social maladjustment between the two groups should be emphasized. Considering the decidedly negative character of the family background of both the persons examined and their brothers from the control group, the extent of social maladjustment in both groups could have been expected to be similar. On the other hand, it could be assumed that from the very criterion of selection to the main group - that is, from the information that the person in question regularly drank excessively, while there was no such information as to the brothers from the control group - it appears that alcohol is the factor that causes the larger extent of social maladjustment among the persons examined as compared with their brothers from the control group. However, this argument seems doubtful in the light of the data as to the social maladjustment during childhood, when drinking did not as yet come into question. As early as in the childhood, the persons examined manifested symptoms of social maladjustment to a decidedly higher degree than their brothers from the control group. In thus seems more probable that the larger intensity both of drunkness, and of other symptoms of social maladjustment is based on the personality characteristics, which are revealed in the early childhood. It is, however, beyond the limits of the present study to supply documentary evidence for this argument or to point out - on the basis of the empirical data - some individualistic characteristics influencing the subsequent social maladjustment; it will be accomplished in another study. This problem was, however, worthy of attention, being important for the theory as well as for practice, all the more so as the trend now prevails to take into account first of all the environmental factors in preventive and corrective treatment. The material presented above seems to suggest that the extent of social maladjustment among different persons with equally negative family backgrounds is influenced at least to the same and perhaps even greater degree by individual psychological than by environmental factors.